The Psychological Impact and Associated Factors of COVID-19 on the General Public in Hunan, China - Shi C; Guo Z; Luo C; Lei C; Li P (Dove Medical Press, 2020)
Chunhong Shi,1 Zhihua Guo,2 Chan Luo,3 Changbin Lei,4 Pan Li1 1School of Nursing, Xiangnan University, Chenzhou 423000, People’s Republic of China; 2Nursing Department, Changsha Health Vocational College, Changsha 410100, People’s Republic of China; 3Nursing Department, The First Affiliated Hospital of University of South China, Hengyang 421001, People’s Republic of China; 4Clinical Medicine Research Center, Affiliated Hospital of Xiangnan University, Chenzhou 423000, People’s Republic of ChinaCorrespondence: Changbin LeiClinical Medicine Research Center, Affiliated Hospital of Xiangnan University, No. 25 Renmin West Road, Beihu District, Chenzhou, 423000 Hunan, People’s Republic of ChinaTel +86 13762563779Fax +86-735-2223633Email leichangbin@xnu.edu.cnPan LiSchool of Nursing, Xiangnan University, 889 Chenzhou Avenue, Suxian District, Chenzhou, 423000 Hunan, People’s Republic of ChinaTel +86 17773560292Fax +86-735-2325007Email lipan1020@xnu.edu.cnPurpose: This study aimed to assess the psychological impact of the COVID-19 pandemic among the general public in Hunan Province, China, which could help develop psychological interventions and mental health programs.Participants and Methods: This online cross-sectional study recruited 571 participants through snowball sampling between February 2 and February 5, 2020. Data were collected through a general information questionnaire, the Public Emergency Psychological State Questionnaire, the Simple Coping Style Questionnaire, and the Public Disease Awareness on COVID-19 Scale.Results: The total mean score of the public emergency psychological state of the sample was 0.27 (0.31) points, with only 5.78% of participants (n = 33) developing psychological distress. Avoidant coping style and disease awareness were weakly positively correlated (rs = 0.257, p < 0.01) and weakly negatively correlated (rs = − 0.124, p < 0.01) with psychological responses, respectively. There were significant psychological differences among the following variables: occupation, symptoms of fever or fatigue, discernment of the authenticity of COVID-19 information, and level of concern regarding COVID-19 (p < 0.05).Conclusion: The COVID-19 pandemic appears to have had a minor psychological impact on the general population in Hunan Province. However, psychological health promotion in the general public is still required, especially for employees (such as company employees, migrant workers, and businessmen), individuals with COVID-19-like symptoms, limited discernment competence and unconcerned attitudes.Implications: The initiatives for improving psychological health among the general public could focus on delivering COVID-19 knowledge and alleviating avoidant coping styles. Our findings could provide important insight for the development of psychological support strategies in China, as well as in other places affected by the epidemic.Keywords: coping style, coronavirus disease 2019, disease awareness, psychological health, public health emergency